Culture and leadership : from approximation towards symbiosis - Fircks, Enno von (Advances in cultural psychology., 2025)
Culture and Leadership: From Approximation Towards Symbiosis is a unique collection of international scholarly work that explores the connection between culture and leadership. The authors, coming from various theoretical and practical backgrounds, introduce new foundational ideas for studying leadership. They discuss how leadership can be defined and practiced in a dynamic way, considering both the personal and collective cultures of leaders and followers. This book highlights the importance of understanding the cultural context in which leadership occurs. It emphasizes that effective leadership involves more than just individual traits or behaviours; it requires an appreciation of the cultural dynamics at play. By examining these interactions, the authors provide valuable insights into how leadership can be more effectively understood and applied in different cultural settings.